Sexual harassment in public places of Quito: challenges for a “safe city” - Morales Alfonso, Liudmila; Quiroz del Pozo, Nathalia; Ramírez, Graciela (FLACSO - Sede Ecuador, 2016)
Reflections about city, women and security draw reflexive axes for academia, and for the design and implementation of public politics. To prevent and address the manifestations of violence, as varied as the power relations that they embody, has proven to be a difficult and challenging task. This article analyzes how the subjective aspects of sexual harassment pose challenges for the integrity of public politics to eradicate it. It is based on the experiences of harassment during their transit through the public space of three women, in Quito, one of the five cities chosen for the pilot initiative of UN Women "Safe Cities and Safe Public Spaces". Also, it examines the role of such subjective aspects in the interaction of the Protocol for action in cases of sexual violence in the integrated passenger system of Quito and the Integral Penal Code, which raises debates about the role of gender representations in the design and implementation of public politics, the intersection between national and local responsibilities, the role of the State facing gender violence and the symbolic value of crimes and contraventions, for the recognition of its manifestations.